MALAYSIA RESPOND TO INDONESIA POLICY OF SINGKING ILLEGAL FISHING PERSECUTANT SHIP IN RIAU ISLAND PROVINCE - Aulia, Mauludy; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Indonesia is an archipelago state composed of 1/3 of the land region and 2/3 oceans region. Indonesia has realized its own potential, Riau Island as region that 95 % concist of ocean is rich of fish supply but recently the fish population is under threat due to Illegal Fishing activity. Statistic say for 4 years from 2011- 2014 the the fishing production on this Province are keep dropping. Based on this fact Indonesia as mandated by its own law using the singking the persecutant ship policy to make a shock therapy effect to illegal fishing persecutant in Indonesia and to warn them not tokeep its activity. The policy success, in 2015 fish stock rising in Riau island Province and there is a rise in the export income. Many countries respond to this policy especially to countries were their citizen become the illegal fishing persecutant in Riau island Province. The top illegal fishing persecutant are Thailand, Veitnam, and Malaysia. But Malaysia actively respond to this policy because they try to get new information to know what are law sentenced to their citizen due to illegal fihisng activity in Riau Island Province.This research uses a neo-realism perspectife which is supported by foreign policy theory. This study also used a nation-state analysis level with a research focus on the Malaysia respond to Indonesia Sinking illegal fishing persecutant policy in Riau Island Province, and all of data, arguments, facts in this research afterwards using a qualitative explanation method.This research then formulates the answer of the research question related to how Malaysia respond to Indonesia Sinking Illegal Fishing Persecutant Ship in Riau Island Province with 3 indicators : Malaysia actively coordinating with Indonesia in Illegal Fishing persecutant information, Malaysia giving an Advocation help to their citizen detained by Indonesia related to Illegal fishing activity, and Repatriation in Riau Island on 2017 as symbol Malaysia acknowledge Indonesia Sovereignity and warn their citizen not to commit activity that against Indonesia law especially in Fisheries.Keywords: Respond, Policy, Illegal Fishing, Repatriation, Coordination.